Selenium content of native bluestem pastures - Harbers, L.H.; Sapienza, D.A.; Schwanke, L.; Kazemi, S.M.; Smith, E.F. (Kansas State University. Agricultural Experiment Station, 2011)
We used steers with esophageal cannulas to measure selenium in burned and unburned bluestem pastures between May and September. Individual variation among steers sampled varied as much as two fold in selenium content. All values were considered adequate for cattle.
Keywords: Beef; Selenium content; Bluestem pastures